SPEECH ACTS IN DISNEY ANIMATED MOVIE: CINDERELLA 3 A TWIST IN TIME - Thao Quoc Tran; Thanh Vinh Tran (Universitas Bunda Mulia, 2022)
Speech act, one form of linguistic expression, plays a vital role in expressing speaker’s meaning, so understanding the underlying meaning can help to avoid misunderstanding in daily communication situations in general and in movies in specific. This study aims to analyse the types of speech acts performed by characters in the Cinderella 3: A Twist in Time. It adopted Searle's (1983) model of speech acts for data analysis. The findings reveal that 11 characters performed 854 speech acts to indicate five types of speech acts, namely representative, directive, expressive, commissive and declarative. The representatives were most employed, followed by directives, and expressives. The least used illocutionary acts were commissives and declaratives. Regarding the language function, it is found that the most common functions were stating, ordering and calling which were performed mostly by Cinderella, Prince Charming, Anastasia, and Tremaine. This paper suggests some implications for English language teaching and learning in terms of pragmatics.